Strategies to improve the mechanical properties of starch-based materials: plasticization and natural fibers reinforcement - Lopez-Gil, Alberto; Rodriguez-Perez, Miguel Ángel; De Saja, José Antonio; Bellucci, Felipe Silva [UNESP]; Ardanuy, Monica (Assoc Brasil Polimeros, 2014)
Biodegradable polymers are starting to be introduced as raw materials in the food-packaging market. Nevertheless, their price is very high. Starch, a fully biodegradable and bioderived polymer is a very interesting alternative due to its very low price. However, the use of starch as the polymer matrix for the production of rigid food packaging, such as trays, is limited due to its poor mechanical properties, high hidrophilicity and high density. This work presents two strategies to overcome the poor mechanical properties of starch. First, the plasticization of starch with several amounts of glycerol to produce thermoplastic starch (TPS) and second, the production of biocomposites by reinforcing TPS with promising fibers, such as barley straw and grape waste. The mechanical properties obtained are compared with the values predicted by models used in the field of composites; law of mixtures, Kerner-Nielsen and Halpin-Tsai. To evaluate if the materials developed are suitable for the production of food-packaging trays, the TPS-based materials with better mechanical properties were compared with commercial grades of oil-based polymers, polypropylene (PP) and polyethylene-terphthalate (PET), and a biodegradable polymer, polylactic acid (PLA).
Keywords: Biodegradable; Starch; Thermoplastic starch; Biocomposites; Food packaging; Natural fibers; Barley; Grape